Decoding Respiratory Distress: A Yogatantrayukti Perspective - Suraksha .; Sri Nagesh K A (RGUHS Journal of AYUSH Sciences)
Respiratory distress is a condition in which the person experiences difficulty in breathing due to various infective or obstructive pathologies involving the respiratory system. Respiratory distress is often a final common pathway for various life-threatening conditions regardless of underlying cause. Hence understanding the pathology behind the presentation of respiratory distress is crucial as it is a common presenting symptom prior to death and analyzing it promptly can make a significant difference in providing high quality care for improving patientrsquos outcome. Decoding of respiratory distress is done by using Yogatantrayukti which is one of the study tools used to understand the concept of shvaasa explained in Hikkashvaasachikitsitam Adhyaya of Charaka samhita in Ayurveda. Yogatantrayukti offers structured learning approach to understand the pathology of respiratory distress which is termed as lsquoshvaasarsquo in Ayurveda. A complex and diverse perspective of shvaasa as primary disease and as a secondary symptom to any systemic disease is simplified by Yogatantrayukti. An obstructive pathology in digestive system or excretory system causes respiratory distress. Hence keen observation of these systems is also necessary while managing respiratory system. Molecular and clinical pathology of shvaasa is understood by applying yogatantrayukti to different types of shvaasa and anatomical pathology is understood by studying verses related to the causes of shvaasa.